O olhar da imprensa sobre Autos de Resistência: posicionamentos e estratégias linguísticas adotados pelo jornal Agora São Paulo em 2012 - Silva, Alvaro Magalhães Pereira da (2016)
What is the enunciative position that the press assumes in regard to the veracity of occurrences of resistance of individuals killed in police operations in cases that the Judiciary Police registers as “Resisting Arrests”? This is the main topic that this research deals with. It has two main objectives: (a) to identify the position the press takes up, in its discourse, when facing the veracity of occurrences of resistance in the mentioned cases; (b) to describe the linguistics strategies the press employs to make its stand. Evidences chosen for analysis were collected from the newspaper Agora São Paulo. The analysis, based upon the Scandinavian Theory of Linguistic Polyphony (ScaPoLine), indicates that the most frequent press enunciative position consists in deeming the veracity of resistance possible, but not certain. For every three occurrences of such position there are two in which resistance is accepted. Cases rejecting the veracity of resistance have not been found. As the State certifies the veracity of the resistance in cases registered as “Resisting Arrests”, it has been possible to conclude that the press tries to state, with partial success, a skeptical outlook towards the State, but does not challenge it. As for the linguistics strategies, this research has detected, in the most predominant position of the press discourse, the presence of a discursive being that is not identified with the press and that saturates the source of the point of view which assumes the resisting arrests as true. Thanks to a such discursive being the press sets up a non-responsibility link between the press itself and the mentioned point of view. To enact such a discursive being the press employs two linguistic marks: the adjective “suposto” as enunciation modalizer and the verbum dicendi “dizer” as inquit of indirect discourse. The description of such linguistics strategies substantiated the conclusions of this research regarding the identified enunciatives positions, enriching discussions about the role of the text in discourse